2017
DOI: 10.1136/oemed-2017-104458
|View full text |Cite
|
Sign up to set email alerts
|

Internet-based stress management for distressed managers: results from a randomised controlled trial

Abstract: ObjectiveThe aim of this randomised controlled trial (RCT) was to evaluate the efficacy of a guided internet-based stress management intervention (iSMI) among distressed managers compared with a attention control group (AC) with full access to treatment-as-usual.MethodA total sample of 117 distressed managers, mainly employed in the healthcare, IT, communication and educational sector, were randomised to either iSMI (n=59) or an AC group (n=58). The iSMI consisted of eight modules including cognitive behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 53 publications
1
50
0
6
Order By: Relevance
“…The iStress stress management therapy programme developed by Andersson and colleagues has been shown to be effective in several trials [8,10]. It was adapted for people with PTSD and includes psycho-education about PTSD, training in problem-solving and training in techniques for stress reduction and coping with PTSD symptoms such as applied relaxation training, challenging irrational thoughts, mindfulness and training to improve sleep efficiency, as well as exposure to avoided situations.…”
Section: Istress-ptsdmentioning
confidence: 99%
See 2 more Smart Citations
“…The iStress stress management therapy programme developed by Andersson and colleagues has been shown to be effective in several trials [8,10]. It was adapted for people with PTSD and includes psycho-education about PTSD, training in problem-solving and training in techniques for stress reduction and coping with PTSD symptoms such as applied relaxation training, challenging irrational thoughts, mindfulness and training to improve sleep efficiency, as well as exposure to avoided situations.…”
Section: Istress-ptsdmentioning
confidence: 99%
“…Given the large number of people suffering from PTSD, it is, therefore, desirable to develop more efficient forms of treatment delivery that can be widely accessed, and online treatment delivery appears to be a promising alternative to face-to-face therapy. There is initial evidence that therapist-assisted, Internet-based psychological treatments are effective for PTSD [8][9][10][11][12][13]. In a meta-analysis based on 11 trials and 1139 participants, Sijbrandij et al [14] reported an average betweengroup effect size at post treatment of d = 0.71 compared to wait-lists or treatment as usual.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta‐analysis has shown positive effects for CBT when treating occupational stress (Richardson & Rothstein, ). For patients with clinical levels of stress and exhaustion, meta‐analyses have shown no effect of treatments (Ahola, Toppinen‐Tanner, & Seppänen, ; Arends, Bruinvels, Rebergen et al ., ; Perski, Grossi, Perski, & Niemi, ), although some studies indicate positive effects (i.e., Lindsäter, Salomonsson, Santoft et al ., ; Persson Asplund, Dagöö, Fjellström et al ., ). The relatively limited knowledge of how to deal with stress‐related disorders stands in remarkable contrast to anxiety disorders, depression and insomnia, where there is strong empirical support for cognitive behavioural therapy (CBT) regarding symptom reduction (Hofmann, Asnaani, Vonk, Sawyer, & Fang, ).…”
Section: Introductionmentioning
confidence: 99%
“…Intervensi pengelolaan stres berbasis web dan komputer juga efektif dan berpotensi mengurangi stres dalam skala besar (Heber et al, 2017). Selain itu, juga terbukti efektif dari segi waktu yang dibutuhkan untuk proses terapi dan efek dari terapi (Persson Asplund et al, 2017).…”
unclassified